MO329THE GENETIC DELETION OF THE DUAL SPECIFICITY PHOSPHATASE 3 (DUSP3) ATTENUATES KIDNEY DAMAGE FOLLOWING ISCHEMIA/REPERFUSION INJURY IN MOUSE. (29th May 2021) - Khbouz, Badr; Rowart, Pascal; Poma, Laurence; Bottner, Martina; Bolen, Géraldine; Rahmouni, Souad; Theilig, Franziska; Jouret, François
Abstract: Background and Aims: Dual Specificity Phosphatase 3 (DUSP3) is a positive regulator of the innate immune response in case of sepsis, but its role in the ischemic damage is unknown. Here, we study (i) whether and where DUSP3 is expressed in the renal parenchyma, and (ii) whether its genetic deletion in Dusp3 systemic knock-out ( Dusp3 -/- ) mice attenuates the I/R-associated inflammation and injury. Method: Experiment 1: Ten C57BL/6 male WT and Dusp3 -/- mice underwent right nephrectomy and left renal ischemia for 30 minutes followed by a reperfusion of 48 hours. Blood and kidneys were collected. Renal function was assessed upon I/R biomarkers, i.e. blood urea nitrogen (BUN) and creatinine (SCr). Expressions of inflammatory and immune markers were comparatively quantified at both mRNA (real-time qPCR) and protein (immuno-blotting and –staining) levels in ischemic vs. non-ischemic kidneys in Dusp3 WT vs. KO mice. Experiment 2: Ten C57BL/6 male WT and Dusp3 -/- mice were anesthetized. Renal Doppler ultrasound was performed to assess the renal resistivity index (RRI). The expression of CD31 and VEGF vascular markers was quantified by the means of real-time qPCR and and immuno-staining (FiJi software). Results: Experiment 1: An immuno-reactive signal for DUSP3 was detected in the glomeruli (in co-localization with nephrin) and in Meca-32-positive endothelial cells of both outer and inner medulla of mouse non-ischemic WT kidneys. No significant immunoreactivity for DUSP3 was detected in Dusp3 -/- kidneys. Following renal I/R, the mRNA level of Dusp3 was increased 1.8-fold compared to baseline (p<0.001). Immunoblot quantifications showed a 77-fold increased expression of DUSP3 post renal I/R. Serum levels of I/R biomarkers were significantly lower in Dusp3 -/- compared to WT mice following renal I/R (BUN: 78.4±33.7 vs. 258.9±162.9mg/dL; SCr: 0.1±0.07 vs. 0.8±0.9 mg/dL; p<0.01). At mRNA levels, Dusp3 -/- ischemic kidneys showed a significantly decreased expression level of CD11b, TNF-α, KIM-1, IL-6, IL-1β and caspase-3 compared to controls. The numbers of PCNA-, F4-80- and CD11b-positive cells were significantly reduced in Dusp3 -/- vs WT renal parenchyma post I/R. Experiment 2: The RRI non-invasively measured by ultrasound was lower in Dusp3 -/- group compared to controls (0.56± 0.03 vs. 0.66±0.02; p<0.001). The Dusp3 -/- non-ischemic kidneys were characterized by a 1.8-fold increased surface of CD31-positive cells compared to WT kidneys (p<0.001). At mRNA levels, the Dusp3 -/- kidneys showed significantly increased basal levels of CD31 and VEGF compared to controls. Conclusion: The genetic deletion of DUSP3 is associated with (i) increased renal vascular density, (ii) decreased RRI and (iii) nephroprotection against renal I/R injury.